Comparing Growth and Development and Related Factors in 60-Month-Old Children in Urban and Suburban Kindergartens of Khorramabad, Iran in 2020 - Fatemeh Raoufimehr; Seyedeh Fatemeh Ghasemi; Fatemeh Valizadeh; Mehdi Birjandi; Kimia Karami (Mashhad University of Medical Sciences, 2022)
Background: Developmental disorders in children are classified into different domains and early recognition and treatment can significantly affect children's social and individual functioning.Aim: This study aimed to compare growth, development, and related factors in 60-month-old children in urban and suburban kindergartens of Khorramabad, Iran in 2020.Method: This descriptive study was conducted on 100 children aged 60-month-old in urban and marginal kindergartens in Khorramabad city of Iran in 2020. The tools were Ages and Stages Questionnaire (ASQ) and a demographic characteristics information form with census sampling. Children were evaluated for growth indices such as height, weight and head circumference. Data were analyzed by SPSS statistical software (version 21) and Epi-Info software and T-test, Man-Whitney and Kruskal Wallis tests.Results: The type of kindergarten had a significant relationship with the total score of development (P=0.012) and the domains of gross motor (P=0.007) and personal-social (P=0.004). The mean prevalence of the developmental disorder was estimated 8.7% for urban and 16.1% for subarban children. Developmental delay is not related to gender, delivery type, maternal education, child's history of illness, and economic status of the family (P>0.05) and is related to nutrition and supplement use, the familial marriage of parents, father's addiction and history of developmental disorder (P<0.05).Implications for Practice: Due to the high importance of timely diagnosis and intervention, it is necessary to diagnose and treat developmental disorders at a younger age. Correct planning of managers in the field of nursing can be effective in timely identification of children's developmental disorders and reducing their prevalence.